A Description of Suicides in the Army National Guard During 2007–2014 and Associated Risk Factors. Issue 3 (7th July 2016) - Griffith, James
Abstract : Suicide, due to its increased occurrence in recent years, has been a chief concern of the U.S. military. While there have been many published studies on the topic, conspicuously absent are studies that have included reserve military personnel. To fill this gap, this study reports descriptive statistics of personnel information and events surrounding 706 Army National Guard suicides that had occurred from 2007 through 2014. Comparative personnel information for random samples of nonsuicides for similar years (8 years, 1, 000 cases per year) allowed examining factors associated most with suicide. Findings were very similar to those observed in the active duty Army and civilian populations. Primary risk factors for suicide were as follows: age (young), gender (male), and race/ethnicity (White). Most suicides occurred in nonmilitary status (86%) involving personal firearms (72%). Most frequent events surrounding the suicide were as follows: poor military performance (36% of all suicides), parent–family relationship problems (28%), substance abuse (27%), past behavioral health problem (20%), current behavioral health problems (10%), income problems (22%), and full‐time employment problems (18%). Implications of findings for suicide prevention are discussed.